Detection of Porcine Respirovirus 1 (PRV1) in Poland: Incidence of Co-Infections with Influenza A Virus (IAV) and Porcine Reproductive and Respiratory Syndrome Virus (PRRSV) in Herds with a Respiratory Disease - Aleksandra Woźniak; Piotr Cybulski; Lilla Denes; Gyula Balka; Tomasz Stadejek (Viruses, 2022)
Porcine respirovirus 1 (PRV1) is also known as porcine parainfluenza virus 1 (PPIV1). The prevalence and the role of PRV1 infections for pig health is largely unknown. In order to assess the PRV1 prevalence in Poland, nasal swabs and oral fluids collected from pigs from 30 farms were examined with RT real-time PCR. Additionally, IAV and PRRSV infection statuses of PRV1-positive samples were examined. The results showed that the virus is highly prevalent (76.7% farms positive) and different patterns of PRV1 circulation in herds with mild–moderate respiratory disease were observed. Co-infections with IAV and PRRSV were infrequent and detected in 8 (23.5%) and 4 (11.8%) out of 34 PRV1-positive nasal swab pools from diseased pens, respectively. In one pen PRV1, IAV, and PRRSV were detected at the same time. Interestingly, PRV1 mean Ct value in samples with co-infections was significantly lower (29.8 ± 3.1) than in samples with a single PRV1 infection (32.5 ± 3.6) (p < 0.05), which suggested higher virus replication in these populations. On the other hand, the virus detection in pig populations exhibiting respiratory clinical signs, negative for PRRSV and IAV, suggests that PRV1 should be involved in differential diagnosis of respiratory problems.